2020
DOI: 10.1007/s10903-019-00968-5
|View full text |Cite
|
Sign up to set email alerts
|

Living Conditions and the Mental Health and Well-being of Refugees: Evidence from a Large-Scale German Survey

Abstract: Refugees are at an increased risk of mental health problems and low subjective well-being. Living circumstances in the host country are thought to play a vital role in shaping these health outcomes, which, in turn, are prerequisites for successful integration. Using data from a representative survey of 4325 adult refugees who arrived in Germany between 2013 and 2016, we investigated how different living conditions, especially those subject to integration policies, are associated with psychological distress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 60 publications
(72 reference statements)
7
132
2
5
Order By: Relevance
“…On the depression subscale of the MHI-18, where higher scores from a total score of 0 to 100 indicate better mental health, females showed a depression mean score of 14.47 (SD = 4.84) (59). In the study by Walther et al (58), participants reported a mean value of 3.14 on the Patient Health Questionnaire for Depression and Anxiety [PHQ-4; (79)], indicating mild psychological distress on average in the past 2 weeks which was higher than the mean score of 1.76 previously determined as the rate for the general German population (80). On the Mental Health Component Summary Scale (MCS), which indicates "a state of mental health well-being" with a total score from 0 to 100, with higher scores indicating better mental health, mean scores of 47.9 and 49.17 were recorded, indicating lower mental health on average, especially among females (M = 46.1), than in the host population (56,57).…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 91%
See 1 more Smart Citation
“…On the depression subscale of the MHI-18, where higher scores from a total score of 0 to 100 indicate better mental health, females showed a depression mean score of 14.47 (SD = 4.84) (59). In the study by Walther et al (58), participants reported a mean value of 3.14 on the Patient Health Questionnaire for Depression and Anxiety [PHQ-4; (79)], indicating mild psychological distress on average in the past 2 weeks which was higher than the mean score of 1.76 previously determined as the rate for the general German population (80). On the Mental Health Component Summary Scale (MCS), which indicates "a state of mental health well-being" with a total score from 0 to 100, with higher scores indicating better mental health, mean scores of 47.9 and 49.17 were recorded, indicating lower mental health on average, especially among females (M = 46.1), than in the host population (56,57).…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 91%
“…Seventeen different instruments were used in these studies. In six studies, questionnaires were completed by participants (self-report) (50,52,53,55,61,62), while the studies by Comtesse and Rosner (54) and Kaltenbach et al (60) used semi-structured clinical interviews, and five studies conducted computer-assisted face-to-face interviews (51,(56)(57)(58)(59). All instruments used in the studies and their validity are presented in Supplementary Table A3.…”
Section: Prevalence Of Psychological Distressmentioning
confidence: 99%
“…According to the analysis, the source of stress most frequently named by migrants is their inability to reunite with their family. Recently, Walther et al (2019) have confirmed the effects of family separation on stress levels and wellbeing, using a comparatively large sample of refugees in Germany.…”
Section: Review Of the Literaturementioning
confidence: 88%
“…This is justified by the aspects that affect the wellbeing of refugees or asylum seekers, as they experience a displacement processes, the loss of the feeling of belonging to a geographical space, the distance from their family and cultural environment, and their exposure to situations of violence and xenophobia [ 50 , 51 ]. There are specific risks and exposures which often occur during the migration trajectory [ 52 ] which cause a prevalence of high levels of distress, life dissatisfaction [ 51 ], anxiety, depression, and suicidal ideation [ 53 , 54 ]. It is possible to infer that the subjective aspects of the psychological suffering of refugees are intrinsically related to the feelings of exclusion and the methods of oppression and violence they face.…”
Section: Science Mapping Of Human Rightsmentioning
confidence: 99%